IMPLEMENTASI MODEL PANTING UNTUK MENINGKATKAN KETERAMPILAN PERCAYA DIRI SISWA PADA PELAJARAN BAHASA INDONESIA - Ghina Muthia Afifah; Ari Hidayat; Akmad Riandy Agusta; Wahdah Refia Rafianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study addresses the issue of low self-confidence among grade 5 students at SDN Sungai Miai 1 in the Indonesian Language learning process. The purpose of this research is to describe the improvement of students’ self-confidence skills through the implementation of the PANTING learning model, which combines Problem Based Learning, Role Playing, and Talking Stick methods. This study employs a mixed-methods approach using Classroom Action Research (CAR) conducted over four sessions. The research subjects consisted of 19 students, including 15 boys and 4 girls. The results show a significant increase in students’ self-confidence, rising from 11% in the first session to 89% in the fourth session. These findings demonstrate that the PANTING learning model effectively enhances students’ self-confidence and learning outcomes in the Indonesian Language subject. Therefore, this model is recommended for use to improve student engagement and confidence in elementary education.